METHOD TO MAKE SIMPLE CALCULATIONS IN A BATCH DISTILLATION COLUMN FOR IDEAL BINARY MIXTURES USING RAYLEIGH EQUATION - Otiniano Cáceres, Manuel Eduardo (2006)
This paper presents a simple method for calculation on a column of binary batch rectification with rectification, using the Rayleigh equation in the two main operating modes: constant, variable reflux reflux.